2022
DOI: 10.1097/ju.0000000000002261
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Muscle-Invasive Bladder Cancer with Nonluminal Subtype Derive Greatest Benefit from Platinum Based Neoadjuvant Chemotherapy

Abstract: PurposeNeoadjuvant chemotherapy (NAC) prior to radical cystectomy (RC) in patients with non-metastatic muscle-invasive bladder cancer (MIBC) confers an absolute survival benefit of 5-10%. There is evidence that molecular differences between tumors may impact response to therapy, highlighting a need for clinically validated biomarkers to predict response to NAC. Materials and MethodsFour bladder cancer cohorts were included. Inverse probability weighting was used to make baseline characteristics (age, sex, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…Last year, Lotan and colleagues published a statistical meta-analysis of response and outcome for NAC-treated and untreated patients from four cohorts profiled with the Genomic Subtyping Classifier (GSC) [ 35 ], of which three were previously reported as original and full-length publications. The study included data on 247 stage cT2-4N0-3 patients treated with pre-operative chemotherapy and 354 stage cT1-4N0-3 patients who received RC without prior NAC treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Last year, Lotan and colleagues published a statistical meta-analysis of response and outcome for NAC-treated and untreated patients from four cohorts profiled with the Genomic Subtyping Classifier (GSC) [ 35 ], of which three were previously reported as original and full-length publications. The study included data on 247 stage cT2-4N0-3 patients treated with pre-operative chemotherapy and 354 stage cT1-4N0-3 patients who received RC without prior NAC treatment.…”
Section: Resultsmentioning
confidence: 99%
“…While this study adjusted for some variables, it selectively included clinical T1 tumors in the untreated arm and cases with known disseminated disease in the treated arm. Unfortunately, the authors did not report pathologic response information, which further urges caution given that they examined a commercially available biomarker (Decipher ® ) [ 35 ]. Finally, even if these reservations are ignored, the statistical significance of the main finding falls when patients treated with adjuvant chemotherapy are excluded from analysis, something that arguably should have been done from the beginning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, genomic imbalances are widespread in muscle invasive bladder cancers, more frequently than lower grade/stage tumors ( Spasova et al, 2021 ). Understanding the genomic heterogeneity of muscle invasive bladder cancer is now being explored as a potential therapeutic response tool ( Lotan et al, 2021 ), an approach amenable to understanding the consequences of adhesion receptor phenotype heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Lotan el al (page 541) in a multi-institutional study advance these objectives, evaluating a cohort of 601 patients with nonvariant muscle-invasive bladder cancer who underwent transcriptomic profiling based on a commercially available genomic classifier. 1 They found that neoadjuvant chemotherapy was associated with survival benefits in nonluminal subtypes, but not in luminal subtypes. The authors conclude that a genomic classifier may help identify patients with bladder cancer who would benefit most from neoadjuvant chemotherapy.…”
mentioning
confidence: 99%